Truth in pragmatism. Dewey and Brandom face to face - Frápolli, María José (Análisis. Revista de investigación filosófica, 2022)
In this paper, I compare the approach to truth characteristic of pragmatism, often identified with warranted assertability, with the prosentential proposal put forward by Robert Brandom. I argue that Brandom´s is a genuine step forward from pragmatism and analytic philosophy, even though his philosophical take includes classic pragmatist features. Furthermore, I show that Dewey and Brandom coincide in their social kind of naturalism, also supported by evolutionary psychology. I conclude that the essential distinction between truth and warranted assertability cannot be exposed without involving an external perspective, the third-person perspective, which is absent in standard pragmatist approaches to truth.